‘Alien Elections’: Neighboring State News on the 2018 Russian Presidential Elections - Kazun, Anastasia; Kazun, Anastasia; PashakhinПашахин (Journal of Economic Sociology, 2021)
News media tend to reflect voices in the political establishment while covering international events. Is it still true when almost half of the national audience speak the language of the country featured in the coverage? In this paper, we present an analysis of 19.5k news messages collected from Russian-language Ukrainian news outlets covering the 2018 presidential elections in Russia. Using a mixed-method approach (topic modeling and qualitative reading), we identify key topics and stories and evaluate the extent of personalization in the election coverage. We find three central angles: the focus on polls and election results, election preparations in Crimea, and Vladimir Putin’s victory. The elections are linked predominantly to Crimean issues through the date of the elections, each candidate’s stance on the subject, the election management in the region, and other countries’ reactions to the results. Such coverage has an accusatory bias; it stresses the legal status of the Crimean referendum and the Russian authorities’ actions and reports the pressures on locals by authorities, especially the Crimean Tatars. Not linked directly to Crimea, other angles are less emotionally charged. Political personalization of the discussion has a contradictory nature. On one hand, the overwhelming majority of the messages mention public figures. On the other hand, the coverage of the figures is limited and omits their traits. Moreover, at times, public figures are replaced by non-personalized symbols (e.g., Kremlin, Russian invaders). However, if the former’s coverage is predominantly neutral, the latter’s coverage is more prone to negative and loaded statements.